"The Turk" in the Czech Imagination (1870s-1923) - Malečková, Jitka (Studia Imagologica, 2021)
In "The Turk" in the Czech Imagination (1870s-1923), Jitka Malecˇková describes Czechs' views of the Turks in the last half century of the existence of the Ottoman Empire and how they were influenced by ideas and trends in other countries, including the European fascination with the Orient, images of "the Turk," contemporary scholarship, and racial theories. The Czechs were not free from colonial ambitions either, as their attitude to Bosnia-Herzegovina demonstrates, but their viewpoint was different from that found in imperial states and among the peoples who had experienced Ottoman rule. The book convincingly shows that the Czechs mainly viewed the Turks through the lenses of nationalism and Pan-Slavism - in solidarity with the Slavs fighting against Ottoman rule.